Fresno Chapters of the American Civil Liberties Union and National Lawyers Guild Sanctuary and Civil Liberties Workshop - Watkins, Howard::::::::: (1985)
Panel of Pam Whalen, Richard Criley, American Civil Liberties Union of Northern California Staff Attorney Mark Schlosser and American Civil Liberties Union Chapter Sam Gitchel Television channel 24 microphone on table